Supply and Demand System untuk Hasil Budidaya Ikan Laut Berbasis Website - Dedi Rahman Habibie; Sandy Suwandana (LPPM Universitas Sains dan Teknologi Komputer, 2020)
Information regarding the availability of marine fish cultivation products is important for related business actors because availability will affect prices and the sustainability of the business that is being carried out, one of which is a culinary business that requires a supply of marine fish. In addition, suppliers are also required to be able to meet and balance supply and market needs so that market prices can be maintained stable. The most basic problem is that the order or request process made by business people still requires coming directly to the place to place fish orders. In addition, the availability of fish is not necessarily sufficient. This of course will require a lot of time in the process of ordering or requests made by culinary business people with suppliers. Another problem occurs with suppliers, namely when the harvest from fish farming is ready for harvest, the supplier must also be able to offer it to parties who need fish supplies. The purpose of this study is to design and build a supply and demand system for web-based marine fish cultivation products so that it is expected to facilitate the process of demand and supply of marine fish cultivation products. The method used to analyze the requirements / needs in this study is structured analysis so that the design results are obtained according to user needs.